Povezanost konativnih karakteristika i situacijske ucinkovitosti vrhunskih seniorskih kosarkasa - Sindik, J. (Croatian Sports Medicine Journal, 2012)
The aim of the study was to determine the relationship between the standard and derived parameters of situational performance basketball and the dimensions of the perceived group cohesion, mental strength, multidimensional perfectionism in sport situations and unidimensional perfectionism. Also, we tried to predict all the standard and derived situational basketball performance parameters with all the dimensions of psychological characteristics.The sample of participants from nine basketball team's in A-1 Croatian men's basketball league championship in 2006/2007. was examined. Canonical analysis was performed to determine the correlation between situation-related efficacy parameters and conative characteristics, while we have used complete multiple regression to predict situation-related efficacy parameters with all the dimensions of psychological characteristics. The results showed no statistically significant correlation between a set of conative characteristics and situational set of parameters of efficiency in basketball, as well as no statistically sig ificant prediction, for the standard or derived parameters of situational basketball performance, with all the dimensions of psychological characteristics, or all together, or separately. The few hypothetical interpretations of these results are given. The significant value of a beta-coefficients for individual predictors, as well as the relatively high value of the canonical correlation between two sets of data, is indicating the probability that the correlation could be statistically significant, if the number of respondents was slightly higher.